2021
DOI: 10.3390/ijerph182212189
|View full text |Cite
|
Sign up to set email alerts
|

Collection of Data on Sex, Sexual Orientation, and Gender Identity by U.S. Public Health Data and Monitoring Systems, 2015–2018

Abstract: We aimed to assess Centers for Disease Control and Prevention (CDC) data systems on the extent of data collection on sex, sexual orientation, and gender identity as well as on age and race/ethnicity. Between March and September 2019, we searched 11 federal websites to identify CDC-supported or -led U.S. data systems active between 2015 and 2018. We searched the systems’ website, documentation, and publications for evidence of data collection on sex, sexual orientation, gender identity, age, and race/ethnicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 21 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…2,3 These findings are consistent with a review of US Health Data and monitoring systems which revealed that although most (94.1%) systems collected data on sex, only 5.9% collected data on gender identity. 16 Second, there are a limited number of studies that analyzed differences in sex or gender even when data on demographics of the population surveyed were recorded. This approach is at odds with the recommendations to collect and disaggregate data on sex, gender identify, and other important demographic variables when possible.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 These findings are consistent with a review of US Health Data and monitoring systems which revealed that although most (94.1%) systems collected data on sex, only 5.9% collected data on gender identity. 16 Second, there are a limited number of studies that analyzed differences in sex or gender even when data on demographics of the population surveyed were recorded. This approach is at odds with the recommendations to collect and disaggregate data on sex, gender identify, and other important demographic variables when possible.…”
Section: Discussionmentioning
confidence: 99%
“…A specific example for Module 8 is as follows: instead of three intensive readings on the mismeasurement of gender and sexuality in data collection leading to disparities in the availability of ICOTS11 (2022) Invited Paper -Refereed (DOI: 10.52041/iase.icots11.T1F3) public health data for gender and sexuality minorities (Kress et al, 2021;MacCarthy & Elliott, 2021;Westbrook & Saperstein, 2015), a single video will be assigned that describes basic information regarding gender and sexuality in seven minutes (e.g., Osmosis from Elsevier, 2020). Then students will be asked to think about surveys they have taken and how gender has been represented, and to answer the question "If gender is collected as binary, what repercussions could exist for non-cisgender individuals?"…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…Furthermore, studies show that cities with protective sexual orientation nondiscrimination laws and policies were more likely to collect and report SOGIE data . Despite improved SOGIE data collection in these settings, reporting such data continues to be limited and absent on many federal websites …”
Section: Current State Of Sogie Data Capturementioning
confidence: 99%